2021
DOI: 10.1162/asep_a_00834
|View full text |Cite
|
Sign up to set email alerts
|

Trade and Human Capital in Global Value Chain in Developed and Developing Countries

Abstract: This paper investigates the effects of human capital on bilateral domestic value-added trade in global value chains (GVCs) for 43 countries and 56 sectors. In contrast to previous studies, this paper estimated an approximate gravity model of value-added trade to capture the role of human capital in determining the cross-border production linkages via value-added trade. The results show that the domestic value-added trade flows depend critically on human capital development in both exporting and importing count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Wang, W. et al estimated an approximate gravity model of value-added trade to clarify the impact of human capital on bilateral domestic value-added trade by country and sector. Domestic value-added trade flows are heavily dependent on human capital development in both exporting and importing countries, as well as technological intensity plays an active role in value-added trade in GVCs [11]. Phillips, W. et al showed that the New Crown Pneumonia pandemic has had a huge impact on the global economy, revealing shortcomings in GVCs and demonstrating the challenges of coordinating and vulnerability of cross-sectoral GVCs.…”
Section: Introductionmentioning
confidence: 99%
“…Wang, W. et al estimated an approximate gravity model of value-added trade to clarify the impact of human capital on bilateral domestic value-added trade by country and sector. Domestic value-added trade flows are heavily dependent on human capital development in both exporting and importing countries, as well as technological intensity plays an active role in value-added trade in GVCs [11]. Phillips, W. et al showed that the New Crown Pneumonia pandemic has had a huge impact on the global economy, revealing shortcomings in GVCs and demonstrating the challenges of coordinating and vulnerability of cross-sectoral GVCs.…”
Section: Introductionmentioning
confidence: 99%
“…This industry is the basis of national economic development, especially industrial development [1][2][3][4]. China's equipment manufacturing industry has long been locked in the low end of the global value chain, leading to its low international competitiveness [5][6][7]. The international competitiveness of China's productive service industry is also not high due to its small and fragmented size and the imperfect industrial system [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Ruiqing Haol, Yunxiu Sai and Qian Ren. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14] …”
mentioning
confidence: 99%